The Politics of Waiting: Transnational Identity and Exile in Achy Obejas’ Ruins - Kevin Concannon (Revue LISA)
In her Presidential Address to the American Studies Association, Shelley Fisher Fishkin asks, “What does it mean to be ‘included’ in or ‘excluded’ from the nation?” The question reflects the transnational turn within American Studies, as increased attention to patterns of movement and changing notions of citizenship have led to a sense of indeterminacy over how national belonging is defined. A tension emerges within the transnational as a result, as attempts to re-imagine the fluidity of political belonging are countered by a national rhetoric organized in terms of maintaining division. This tension highlights much of the work of Cuban-born writer Achy Obejas, whose recent novels have focused attention on the challenge of “remembering” Cuba in the United States. In the novel Ruins, Obejas complicates understandings of the nation by conceiving of it in a larger global and temporal context, seeking to historicize the U.S.-Cuban expatriate experience within the broader Jewish diaspora. By constructing this alternative history, Obejas expresses the U.S. expatriate connection to Cuba not in terms of remittances or political debate, but within the larger context of diaspora, separation and forgetfulness, and by doing so, defines Cuban identity through a transnational prism of historical difference and denial.